قراءة ثقافية لخطاب المستشرقين الإسبان، بين مركزية الذات، وهامشية الآخر الأندلسي - أحلام, زيطاري; سعاد, شريف (جامعة الوادي - University of Eloued, 2022)
ملخص: تهدف هذه القراءة النقدية الثقافية لبيان أوجه الخطاب الاستشراقي الإسباني المتعدّدة، وكشف المرجعية الثقافية المضمرة، والتي تتجسد في أنساق ثقافية مختفيّة تحت أقنعة متعددة، لتكوين صورة الذات الإسباني والآخر العربي الأندلسي، وعلاقتهم الثقافية، ولقد اخترنا خطابات المستشرقين الإسبان كموضوع للدراسة والبحث، بواسطة تطبيق آليات القراءة النقدية الثقافية، ونظرية الأنا والآخر ومسألة التقبل والرفض، لمعرفة مدى تأثيرها في الحراك الثقافي، بين فكرة هيمنة ذات المستشرق الإسباني وإقصاء ثقافة الآخر الأندلسي، لنختم بجملة من النتائج أهمها أن خطاب المستشرقين يبرز الكثير من الأنساق الثقافية وصراع بين المركز والهامش، بين المستشرق الإسباني الذي يحاول فرض هيمنته على الآخر العربي الأندلسي ومحو ثقافته وعدم الاعتراف بحضارته، ونسبها للسكان الأصليين لشبه الجزيرة الأيبيرية. Abstract: This study is a critical cultural reading that illustrates the various aspects of Spanish orientalist discourse. It unveils the embedded cultural reference manifesting through several masked cultural patterns. These patterns shape the self’s image, the image of the Andalusian other, and the cultural relationship between them. We opted for Spanish orientalist discourse as a research subject. We applied critical cultural reading principles, Self - Other theory, as well as the question of acceptance and intolerance, to measure the extent to which discourse impacts the cultural movement between Spanish orientalist dominance and the exclusion of the Andalusian other and his culture. T he conclusion comes with several results: Orientalist discourse reflects several cultural patterns that mirror the struggle between center and periphery, between Spanish orientalist and Andalusian other; a struggle through which the former exercises dominance over the latter, through which he deculturizes him, delegitimizes his civilization, and appropriates it to the natives of the Iberian Peninsula. الكلمات المفتاحية الكلمات المفتاحية : الاستشراق الإسباني،، الذات والآخر، النقد الثقافي، الهامش والمركز،القراءة. ; Keywords: Spanish orientalism, Andalusian, Self and other, Cultural critique, Periphery and center, Reading. ملخص: تهدف هذه القراءة النقدية الثقافية لبيان أوجه الخطاب الاستشراقي الإسباني المتعدّدة، وكشف المرجعية الثقافية المضمرة، والتي تتجسد في أنساق ثقافية مختفيّة تحت أقنعة متعددة، لتكوين صورة الذات الإسباني والآخر العربي الأندلسي، وعلاقتهم الثقافية، ولقد اخترنا خطابات المستشرقين الإسبان كموضوع للدراسة والبحث، بواسطة تطبيق آليات القراءة النقدية الثقافية، ونظرية الأنا والآخر ومسألة التقبل والرفض، لمعرفة مدى تأثيرها في الحراك الثقافي، بين فكرة هيمنة ذات المستشرق الإسباني وإقصاء ثقافة الآخر الأندلسي، لنختم بجملة من النتائج أهمها أن خطاب المستشرقين يبرز الكثير من الأنساق الثقافية وصراع بين المركز والهامش، بين المستشرق الإسباني الذي يحاول فرض هيمنته على الآخر العربي الأندلسي ومحو ثقافته وعدم الاعتراف بحضارته، ونسبها للسكان الأصليين لشبه الجزيرة الأيبيرية. Abstract: This study is a critical cultural reading that illustrates the various aspects of Spanish orientalist discourse. It unveils the embedded cultural reference manifesting through several masked cultural patterns. These patterns shape the self’s image, the image of the Andalusian other, and the cultural relationship between them. We opted for Spanish orientalist discourse as a research subject. We applied critical cultural reading principles, Self - Other theory, as well as the question of acceptance and intolerance, to measure the extent to which discourse impacts the cultural movement between Spanish orientalist dominance and the exclusion of the Andalusian other and his culture. T he conclusion comes with several results: Orientalist discourse reflects several cultural patterns that mirror the struggle between center and periphery, between Spanish orientalist and Andalusian other; a struggle through which the former exercises dominance over the latter, through which he deculturizes him, delegitimizes his civilization, and appropriates it to the natives of the Iberian Peninsula.
مقال
Keywords: الذات والالاستشراق الإسباني،،آخر، النقد الثقافي، الهامش والمركز،القراء; ملخص: تهدف هذه القراءة النقدية الثقافية لبيان أوجه الخطاب الاستشراقي الإسباني المتعدّدة، وكشف المرجعية الثقافية المضمرة، والتي تتجسد في أنساق ثقافية مختفيّة تحت أقنعة متعددة، لتكوين صورة الذات الإسباني والآخر العربي الأندلسي، وعلاقتهم الثقافية، ولقد اخترنا خطابات المستشرقين الإسبان كموضوع للدراسة والبحث، بواسطة تطبيق آليات القراءة النقدية الثقافية، ونظرية الأنا والآخر ومسألة التقبل والرفض، لمعرفة مدى تأثيرها في الحراك الثقافي، بين فكرة هيمنة ذات المستشرق الإسباني وإقصاء ثقافة الآخر الأندلسي، لنختم بجملة من النتائج أهمها أن خطاب المستشرقين يبرز الكثير من الأنساق الثقافية وصراع بين المركز والهامش، بين المستشرق الإسباني الذي يحاول فرض هيمنته على الآخر العربي الأندلسي ومحو ثقافته وعدم الاعتراف بحضارته، ونسبها للسكان الأصليين لشبه الجزيرة الأيبيرية. Abstract: This study is a critical cultural reading that illustrates the various aspects of Spanish orientalist discourse. It unveils the embedded cultural reference manifesting through several masked cultural patterns. These patterns shape the self’s image, the image of the Andalusian other, and the cultural relationship between them. We opted for Spanish orientalist discourse as a research subject. We applied critical cultural reading principles, Self - Other theory, as well as the question of acceptance and intolerance, to measure the extent to which discourse impacts the cultural movement between Spanish orientalist dominance and the exclusion of the Andalusian other and his culture. T he conclusion comes with several results: Orientalist discourse reflects several cultural patterns that mirror the struggle between center and periphery, between Spanish orientalist and Andalusian other; a struggle through which the former exercises dominance over the latter, through which he deculturizes him, delegitimizes his civilization, and appropriates it to the natives of the Iberian Peninsula. الكلمات المفتاحية الكلمات المفتاحية : الاستشراق الإسباني،، الذات والآخر، النقد الثقافي، الهامش والمركز،القراءة. ; Keywords: Spanish orientalism, Andalusian, Self and other, Cultural critique, Periphery and center, Reading.